Identification of presumed ancestral DNA sequences of phaseolin in Phaseolus vulgaris - Kami, James A.; Becerra Velásquez, Viviana L.; Debouck, Daniel G.; Gepts, Paul L. (1994)
Common bean (Phaseolus vulgaris) consists of two major geographic gene pools, one distributed in Mexico, Central America, and Colombia and the other in the southern Andes (southern Peru, Bolivia, and Argentina). Amplification and sequencing of members of the multigene family coding for phaseolin, the major seed storage protein of the common bean, provide evidence for accumulation of tandem direct repeats in both introns and exons during evolution of the multigene family in this species. The presumed ancestral phaseolin sequences, without tandem repeats, were found in recently discovered but nearly extinct wild common bean populations of Ecuador and northern Peru that are intermediate between the two major gene pools of the species based on geographical and molecular arguments. Our results illustrate the usefulness of tandem direct repeats in establishing the polarity of DNA sequence divergence and therefore in proposing phylogenies